2022
DOI: 10.1007/s00338-022-02304-0
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of benthic cyanobacterial mats on coral reefs of Koh Tao, Gulf of Thailand

Abstract: Benthic cyanobacterial mats are increasingly reported to cover major coral reef areas. Although suggestions have been made that cyanobacterial mats impair coral reef health in multiple ways, information is lacking regarding the distribution, morphotypical variation and bacterial species composition of these microbial mats. As such, this study aimed to (1) Reveal the bacterial community diversity and composition of different mat morphotypes, (2) Identify the most abundant community members and closely related o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 110 publications
6
5
0
Order By: Relevance
“…The influence of both local and global stressors is driving near-ubiquitous increases in the proportional cover of conspicuous benthic cyanobacterial mats on coral reefs worldwide (reviewed in Ford et al 2018), including increasing the relative cover of spatially discrete, horizontally-spreading mat carpets (de Bakker et al 2017) and vertically tufting cyanobacteria (Ford et al 2021), as well as increasing the duration and magnitude of extensive (i.e., kilometer-scale) benthic bloom events (Hewson et al 2001, Paul et al 2005). Similar to microbial mats found in other systems (Bolhuis et al 2014), cyanobacterial mats found on coral reefs are complex and strongly cooperative microbial consortia (Cissell and McCoy 2021, Stuij et al 2022). Coral reef cyanobacterial mats, while structurally built by phototrophic cyanobacterial taxa, also contain a taxonomically and functionally diverse suite of microbial eukaryotes, heterotrophic bacteria, and viruses (Cissell and McCoy 2021, Stuij et al 2022).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The influence of both local and global stressors is driving near-ubiquitous increases in the proportional cover of conspicuous benthic cyanobacterial mats on coral reefs worldwide (reviewed in Ford et al 2018), including increasing the relative cover of spatially discrete, horizontally-spreading mat carpets (de Bakker et al 2017) and vertically tufting cyanobacteria (Ford et al 2021), as well as increasing the duration and magnitude of extensive (i.e., kilometer-scale) benthic bloom events (Hewson et al 2001, Paul et al 2005). Similar to microbial mats found in other systems (Bolhuis et al 2014), cyanobacterial mats found on coral reefs are complex and strongly cooperative microbial consortia (Cissell and McCoy 2021, Stuij et al 2022). Coral reef cyanobacterial mats, while structurally built by phototrophic cyanobacterial taxa, also contain a taxonomically and functionally diverse suite of microbial eukaryotes, heterotrophic bacteria, and viruses (Cissell and McCoy 2021, Stuij et al 2022).…”
Section: Introductionsupporting
confidence: 76%
“…Similar to microbial mats found in other systems (Bolhuis et al 2014), cyanobacterial mats found on coral reefs are complex and strongly cooperative microbial consortia (Cissell and McCoy 2021, Stuij et al 2022). Coral reef cyanobacterial mats, while structurally built by phototrophic cyanobacterial taxa, also contain a taxonomically and functionally diverse suite of microbial eukaryotes, heterotrophic bacteria, and viruses (Cissell and McCoy 2021, Stuij et al 2022). Expanding cover of cyanobacterial mats generates complex feedback loops with other major causes of reef degradation, and may exacerbate the velocity and magnitude of existing trajectories of reef decline (Ethan C. Cissell and McCoy 2022).…”
Section: Introductionsupporting
confidence: 76%
“…Benthic cyanobacterial mats (BCMs) are becoming increasingly dominant members of coral reef communities worldwide due to the influence of both local and global stressors (Cissell & McCoy, 2022a; de Bakker et al, 2017; Ford et al, 2018). We define coral reef BCMs as a functional grouping that broadly encompasses taxonomically and functionally rich, conspicuous benthic consortia primarily comprised of prokaryotic members of the phyla Cyanobacteria (dominating the construction and maintenance of mat structural complexity), Proteobacteria, and Bacteroidetes (Cissell & McCoy, 2021; Stuij et al, 2022). The proliferation of BCMs on coral reefs is both a product of and itself exacerbates reef degradation, with feedback among BCM cover and major drivers of reef decline such as shifting reef carbon chemistry and coral disease transmission (Brocke, Polerecky, et al, 2015; Cissell et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Benthic cyanobacterial mats (BCMs) are complex, layered structures with high structural, spatial, and temporal heterogeneity (Figure 1). These BCMs consist of a consortium of bacteria, archaea, eukarya, viruses, and more, with the Cyanobacteria, Proteobacteria, and Bacteroidetes often dominating these communities (e.g., Cissell & McCoy, 2021;Stuij et al, 2023). Benthic cyanobacterial mats are vertically stratified in temperate marine (e.g., Carreira et al, 2015), hypersaline (e.g., Dillon et al, 2009), and freshwater systems (e.g., Borovec et al, 2010;Velázquez et al, 2017), while those in tropical marine systems have more distinct horizontal spatial differences (e.g., Cissell & McCoy, 2021).…”
Section: Introductionmentioning
confidence: 99%